Peran Satgas Pengolahan Sampah di Pantai Suak Baru Simeulue dalam Pemanfaatan Kompos dari Daun dan Ranting untuk Produktivitas Pertanian - Darsan, Herri; Suyono, Eko Agus; Nurcahyo, Raden Wisnu; Kurniawan, Adhy; Muslimah, Yuliatul; Hermi, Rudi; Haikal, Muhammad; Irja, Muhammad; Baroqah, Nuzul (Universitas Teuku Umar, 2024)
Suak Baru Village in Simeulue Regency, Aceh, faces challenges in waste management, particularly in the tourist area of Suak Baru Beach. This situation is exacerbated by the lack of adequate waste management facilities, leading to environmental pollution that threatens public health and the area's attractiveness to tourists. The design of this community service program aims to increase the community's preparedness for the adoption of environmentally friendly waste management technologies, specifically composting and plastic recycling methods. The activities include socialization, training, technology implementation, and program sustainability evaluation. The program's results show a significant improvement in the community’s understanding of effective waste management. The use of organic and plastic shredding technology successfully reduced waste volume and created economic value through recycled products. It is hoped that government support and active community participation will ensure the sustainability of this program for a cleaner, healthier environment and improved local economic welfare.